(untitled) (Ius Novum, 2025)
This article discusses the exemption from the remainder of the penalty of limitation of liberty (non-custodial penalty) under Article 83 of the Penal Code, a legal institution that plays a significant role in criminal policy. It is intended to encourage convicted persons to comply with the law not only during the execution of the penalty but also after exemption, once part of the penalty has been served. However, this objective may not always be achieved due to the absence of additional instruments for influencing the conduct of convicted persons following exemption. The definitive nature of exemption, which precludes any further action in the event of a violation of the legal order by the exempted person, has led to a de lege ferenda proposal to make this institution conditional. The article analyses the purpose and legal nature of exemption, the conditions for its application (serving part of the sentence, compliance with the legal order, fulfilment of obligations imposed on the convicted person, penal measures, compensatory measures, and forfeiture), the sentencing procedure, and the consequences of exemption leading to recognition of the sentence as served.